2013
DOI: 10.1021/cn300234z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-HT1A Receptor Stimulation on D1 Receptor Agonist-Induced Striatonigral Activity and Dyskinesia in Hemiparkinsonian Rats

Abstract: Accumulating evidence supports the value of 5-HT 1A receptor (5-HT 1A R) agonists for dyskinesias that arise with long-term L-DOPA therapy in Parkinson's disease (PD). Yet, how 5-HT 1A R stimulation directly influences the dyskinetogenic D1 receptor (D1R)-expressing striatonigral pathway remains largely unknown. To directly examine this, one cohort of hemiparkinsonian rats received systemic injections of Vehicle + Vehicle, Vehicle + the D1R agonist SKF81297 (0.8 mg/kg), or the 5-HT 1A R agonist ±8-OH-DPAT (1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 74 publications
2
17
0
Order By: Relevance
“…Furthermore, 8-OH-DPAT did not reverse SKF81297-induced decreases in high beta power in contrast to its effects when administered after L-dopa. Moreover, in contrast to its moderate reduction of high gamma power, and in agreement with previous reports (Dupre et al, 2007, 2013), 8-OH-DPAT dramatically reduced SKF81297-induced ALO AIMs (Fig. 5D).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, 8-OH-DPAT did not reverse SKF81297-induced decreases in high beta power in contrast to its effects when administered after L-dopa. Moreover, in contrast to its moderate reduction of high gamma power, and in agreement with previous reports (Dupre et al, 2007, 2013), 8-OH-DPAT dramatically reduced SKF81297-induced ALO AIMs (Fig. 5D).…”
Section: Resultssupporting
confidence: 93%
“…5H). This effect was associated with increased rotational activity that is distinct from ALO AIMs (Breger et al, 2013) and often observed with this treatment combination (Dupre et al, 2007, 2013). Furthermore, 8-OH-DPAT did not reverse SKF81297-induced decreases in high beta power in contrast to its effects when administered after L-dopa.…”
Section: Resultsmentioning
confidence: 76%
“…In support, compounds that reversed parkinsonian motor deficits frequently induced contralateral rotations [34, 35]. Additionally, compounds with low dyskinesia liability, such as bromocriptine, induced strong contralateral circling behavior [36, 37] and many compounds that effectively reduce dyskinesia often do not alter L-DOPA- or DA agonist- induced rotations [38, 39]. In fact, some antidyskinetic compounds actually enhance or extend rotational behaviors in the 6-OHDA lesioned rat model of PD when given in conjunction with L-DOPA or DA agonists [4042].…”
Section: Discussionmentioning
confidence: 99%
“…Striatal D 1 R stimulation can activate pERK and promote dyskinesia (Feyder et al, 2011; Gerfen et al, 2002; Santini et al, 2010; Papadeas et al, 2004) while 5-HT 1A Rs reduce D 1 R-mediated dyskinesia (Dupre et al, 2011, 2013), suggesting that striatal 5-HT 1A Rs may alter dyskinesia by reducing D 1 R supersensitivity. By contrast, some 5-HT 1A Rs increase pERK by activating the Ras pathway (Raymond et al, 1999) and overactivity of the Ras pathway promotes dyskinesia (Fasano et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, serotonin 1A receptor (5-HT 1A R) agonists reduce both LID and D 1 R-mediated dyskinesia (Bibbiani et al, 2001; Dupre et al, 2008, 2011, 2013). Following DA-depletion, the expression of 5-HT 1A Rs within the striatum and primary motor cortex (M1) increases, an effect further potentiated by L-DOPA treatment (Frechilla et al, 2001; Huot et al, 2012).…”
Section: Introductionmentioning
confidence: 99%